Implementasi Pendidikan Multikultural Dalam Membina Interaksi Sosial Siswa Di SMKN 6 Kabupaten Tebo Provinsi Jambi - Suriyanto (4, 2026)
This study aims to describe and analyze the implementation of multicultural education in fostering student social interaction at State Vocational High School 6, Tebo Regency, Jambi Province. The background of this study is based on the reality of diverse social, cultural, and religious backgrounds of students, which demands an educational approach capable of fostering tolerance, mutual respect, and social justice within the school environment. Multicultural education is viewed as a strategic approach to fostering harmonious and inclusive student social interactions. This study employed a qualitative approach with a descriptive approach. Data collection was conducted through observation, in-depth interviews, and documentation. Research informants consisted of the principal, teachers, educational staff, and students who were selected purposively. Data analysis used the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and technical triangulation. The results indicate that the implementation of multicultural education at State Vocational High School 6, Tebo Regency, has been integrated into the learning process, school culture, and student social interactions. Teachers play an active role in instilling the values ​​of tolerance, justice, and respect for diversity through dialogic and inclusive learning methods. The implementation of multicultural education has a positive impact on students' social interactions, characterized by increased mutual respect, openness in social interactions, polite communication, and the ability to work together in diverse environments. Abstrak Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis implementasi pendidikan multikultural dalam membina interaksi sosial siswa di SMK Negeri 6 Kabupaten Tebo Provinsi Jambi. Latar belakang penelitian ini didasarkan pada realitas keberagaman latar belakang sosial, budaya, dan agama peserta didik yang menuntut adanya pendekatan pendidikan yang mampu menumbuhkan sikap toleransi, saling menghargai, dan keadilan sosial dalam lingkungan sekolah. Pendidikan multikultural dipandang sebagai pendekatan strategis dalam membangun interaksi sosial siswa yang harmonis dan inklusif. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi. Informan penelitian terdiri atas kepala sekolah, guru, tenaga kependidikan, dan siswa yang dipilih secara purposif. Analisis data menggunakan model analisis interaktif Miles dan Huberman yang meliputi tahap reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data dijamin melalui teknik triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa implementasi pendidikan multikultural di SMK Negeri 6 Kabupaten Tebo telah terintegrasi dalam proses pembelajaran, budaya sekolah, serta interaksi sosial siswa. Guru berperan aktif dalam menanamkan nilai-nilai toleransi, keadilan, dan penghargaan terhadap keberagaman melalui metode pembelajaran yang dialogis dan inklusif. Implementasi pendidikan multikultural tersebut berdampak positif terhadap interaksi sosial siswa, yang ditandai dengan meningkatnya sikap saling menghargai, keterbukaan dalam pergaulan, komunikasi yang santun, serta kemampuan bekerja sama dalam lingkungan yang beragam.